Aneurysms and pseudoaneurysms of saphenous vein coronary artery bypass grafts. Issue 5 (1st May 1998) - Le Breton, H; Pavin, D; Langanay, T; Roland, Y; Leclercq, C; Beliard, J M; Bedossa, M; Rioux, C; Pony, J C
Abstract : Aneurysms of saphenous vein grafts to coronary arteries are unusual complications of coronary artery bypass graft (CABG) surgery. Three patients (men aged 47, 62, and 68 years) are presented with spontaneous chest pains 10, 21, and 17 years after CABG surgery. In one case, the saphenous vein graft had eroded into the right atrium and had established a fistula between the graft and the right atrium. Diagnosis of saphenous vein graft aneurysms was confirmed by echocardiography, computed tomography or magnetic resonance imaging, and by arteriography. Two patients were treated surgically, the third by percutaneous coil embolisation followed by balloon angioplasty of the right coronary artery.